Adaptive Interactive Features in the 'Listen To Me' Application to Support Independent Learning for Visually Impaired Children - Dian Pratiwi; Bambang Triraharjo; Aisyatul Vidyah Qori'ah; Ridho Pamungkas Ibnu Surya; Syifa Miftahunnajah (Universitas Pendidikan Mandalika, 2026)
Advancements in information and communication technology have created new opportunities for developing accessible and adaptive learning systems. One promising approach is the use of audio-based learning applications, which substitute visual information with structured auditory instructions. This research aims to develop adaptive interactive features in the ‘Listen to Me” application to enhance the independent learning skills of visually impaired children. The features are designed with three main characteristics: automatic adaptation of material difficulty levels; an audio-based interface that delivers clear instructions and feedback; and dynamic responses that adjust to users’ interaction patterns. The study employed a Research and Development (R&D) approach with a waterfall model, executed through the stages of needs analysis, design, implementation, testing, and evaluation. Expert evaluations of the developed features indicated a very high level of feasibility. Furthermore, the results of limited trials involving the target users (visually impaired children) demonstrated the features’ effectiveness in improving content comprehension, facilitating navigation, and fostering motivation for independent learning. The findings conclude that the adaptive interactive features within the Listen to Me application are feasible, effective, and accessible as a self-learning medium, offering strong potential to support the expansion of inclusive education for visually impaired children.